Pregnancy rate to FTAI in Braford heifers submitted to J-Synch protocol - Reineri, Pablo Sebastian; Coria, María Sumampa; Principi, Santiago Alberto; Punta Perez, Rodrigo; Palma, Gustavo Adolfo (Departamento de Medicina Veterinária da Universidade Federal Rural de Pernambuco, 2023)
The objective of the present work was to evaluate the effect of J-Synch protocol on pregnancy rate (PR) of heifers artificially inseminated after detected estrus (DEAI) or at fixed-time (FTAI). Two hundred ninety-three Braford heifers were used. On day 0, all animals received 2.0 mg of estradiol benzoate administered intramuscularly (IM) and an intravaginal progesterone-releasing device (DIB, 0.5 g). Heifers were assigned to the following group: 1) J-Synch: on day 6, DIB devices were removed and 500 µg of d-Cloprostenol sodium (d-CS) was administered IM and paint was applied on tail base (tail-paint). On day 9 (60 h after DIB removal), heifers with ? 40% of the tail-paint rubbed off were inseminated. Those not showing estrus by 72 h after DIB removal received 100 µg of GnRH at that time and were FTAI. 2) Conventional: on day 7, DIB devices were removed, and 500 µg of d-CS and 0.5 mg of estradiol cypionate were administered IM and tail-paint. Forty-eight hours after DIB removal, heifers with the tail-paint rubbed off were DEAI. Those not showing estrus by 54 h after DIB removal were FTAI. Pregnancy rate was diagnosed by ultrasonography 30 days after FTAI in all heifers and did not differ between protocols (44.28% and 42.48%, P = 0.673). In both protocols, higher PR was observed in DEAI heifers (P = 0.047). In conclusion, the use of the J-Synch protocol generated similar PR to the Conventional protocol, allowing its use with the same efficiency. Furthermore, the DEAI generated better PR than the FTAI, regardless of the protocol used.